Penguatan Kapasitas KPM PKH dalam Memanfaatkan Familly Development Session di Distrik Sentani, Kabupaten Jayapura - Albertina N. Lobo; Eddy Pattanduk (JURNAL PENGABDIAN PAPUA, 2025)
Dependence on conditional cash social assistance programs from the government is a classic problem and needs to be avoided by increasing the capacity of beneficiary families. The activity of strengthening the capacity of PKH KPM in utilizing family development sessions aims to improve understanding, knowledge, and skills about financial management and family independent businesses, in Sereh village, Sentani district, Jayapura regency. The implementation method includes brainstorming, counseling, group discussions, documentation and evaluation. The results of the implementation of the activity explain that family capacity focuses on finances and work motivation. Sustainable family financial and business management has minimal information and training, after counseling, families prioritize needs, namely the needs of school children, business capital, family social costs, and savings. However, aspects of family commitment and openness to business management are factors that influence family capacity. Collaboration between academics, PKH assistance, and PKH independent families is needed so that beneficiary families are confident in the commitment of the business being developed so that they avoid the acute poverty zone.